THE RELATIONSHIP BETWEEN INTERNET ADDICTION AND SLEEP QUALITY: A LITERATURE REVIEW - Tamala, Riska; Nurlinawati, Nurlinawati; Mulyani, Sri (Program Studi Keperawatan Universitas Jambi, 2024)
Abstract Internet addiction is a compulsive behavior in which individuals fail to control internet use and dependence on the internet. Individuals withinternet addiction are more prone to experience poor sleep quality. Poor sleep quality will cause physical problems, memory and learning disorders, suboptimal performance, mental health problems and are prone to accidents. The purpose of this study was to determine therelationship between internet addiction and sleep quality. This research method uses a literature study approach by searching for articles on the Google scholar database, Garuda Portal, Pubmed and researchgate. The keywords used are internet addiction, sleep quality and internetaddiction and sleep quality. The results obtained 11 articles in accordance with the research topic, 10 of which stated that there was a relationship between internet addiction and sleep quality. The conclusions and suggestions of this study are internet addiction can cause poor sleep quality, so the role of nurses as educators is needed as an effort to prevent internet addiction and its bad impact on sleep quality